Development of analytical method for pesticide residue determination using LC-MS/MS - Prodhan, Mohammad Dalower Hossain; Begum, Afroza; Afroze, Marina; Ahmed, Md. Sultan; Dutta, Nirmal Kumar; Sarker, Debasish (Asian-Australasian Journal of Food Safety and Security, 2022)
This study was initiated to develop an accurate analytical method for the determination of neonicotinoid and organophosphorus insecticide using Liquid Chromatography tandem Mass Spectrometry (LC-MS/MS). Several experiments were conducted to select the parent ion and precusor ion and based on this outcome, the analytical method for the determination of thiamethoxam and dimethoate using LC-MS/MS was developed. The heated electrospray ionization (HESI) mode was used to develop the method. The linearity of the developed analytical method was very good and it was 0.998 for both of the selected pesticides. The optimization of MS/MS parameters has been done properly for both of the selected pesticides through direct infusion of 100 ug/L standard solutions. Asian Australas. J. Food Saf. Secur. 2022, 6 (2), 65-72